A STUDY ON THE PREVAILING SYSTEMS OF MICROFINANCE AND RURAL PRODUCT MARKETING IN INDIA - Surywanshi, Kiran; Dubey, Tapesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Microfinance and rural product marketing are two integral elements of the economic ecosystem in India, especially in rural areas where financial exclusion and market inefficiencies often hinder economic development. Microfinance has provided financial access to underserved populations, primarily women and marginalized groups, enabling them to engage in entrepreneurial activities. At the same time, rural product marketing plays a crucial role in connecting rural producers with urban and global markets. This paper explores the existing microfinance systems and rural product marketing strategies in Indore(MP) district, analyzing their effectiveness, challenges, and the interplay between them. The study also investigates how these systems contribute to poverty alleviation, economic empowerment, and rural development.